The Influence of the Kerapan Sapi Tradition in Madura on the Enforcement of Criminal Law in Article 302 of the Criminal Code - Herowati Poesoko; Abintoro Prakoso; Muhammad Khalid Ali (Wiraraja University, 2024)
In the context of criminal law, although there are formal regulations in force throughout the country, local culture often plays an important role in its implementation. Therefore, understanding the relationship between local culture such as the tradition of cattle frequency and law enforcement based on article 302 of the Criminal Code concerning the persecution of animals is something that needs to be considered in order to ensure effectiveness and justice in the legal system. This study uses a type of socio-legal research which is an interdisciplinary approach that combines normative legal analysis with a sociological perspective. The information collected is descriptive in both written and oral form. The approach is based on the analysis of the philosophical values of the cattle frequency tradition, while the normative juridical helps in making comparisons against laws and regulations relevant to the cattle frequency tradition. The results show that although official authorities such as the police or the courts play a role, customary institutions are still the main place in mediating in resolving a conflict. This indicates that traditional and cultural values occupy an important place in society and influence how society relates to the formal legal system.